2014
DOI: 10.1007/s10811-014-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bubble size on the efficiency and economics of harvesting microalgae by foam flotation

Abstract: The effect of bubble size and rise velocity on the efficiency of a foam flotation microalgae harvesting unit was determined. Three sparger and input airflow combinations were used: (1) limewood sparger with constant airflow, (2) ceramic flat plate sparger with constant airflow and (3) ceramic flat plate sparger with an oscillating airflow. The ceramic sparger with oscillating flow generated the smallest bubbles within the liquid pool and the largest bubbles within the foam phase. This delivered the highest lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Coward et al [25] reported a flotation device which combines dispersed air flotation with foam fractionation to allow harvesting, concentration and physical separation of algal biomass [25]. Foam fractionation uses low pressure spargers for the production of bubbles and may also be used in combination with fluidic oscillation [106]. A 10.2 L dispersed air flotation-foam fractionation was reported to achieve maximum biomass concentration of 14-24 g DCW/L with an energy consumption of 0.015 kWh/m 3 , using a limewood sparger.…”
Section: Flotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Coward et al [25] reported a flotation device which combines dispersed air flotation with foam fractionation to allow harvesting, concentration and physical separation of algal biomass [25]. Foam fractionation uses low pressure spargers for the production of bubbles and may also be used in combination with fluidic oscillation [106]. A 10.2 L dispersed air flotation-foam fractionation was reported to achieve maximum biomass concentration of 14-24 g DCW/L with an energy consumption of 0.015 kWh/m 3 , using a limewood sparger.…”
Section: Flotationmentioning
confidence: 99%
“…A 10.2 L dispersed air flotation-foam fractionation was reported to achieve maximum biomass concentration of 14-24 g DCW/L with an energy consumption of 0.015 kWh/m 3 , using a limewood sparger. When combined with fluidic oscillation, the maximum biomass concentration increased to 28 g DCW/L, and the energy consumption was estimated to be 0.105 kWh/m 3 [25,106]. In other work, the same researchers demonstrated that harvesting algal biomass with cetyltrimethylammonium bromide (CTAB) aided foam flotation, gained higher lipid recoveries, and exhibited a lipid profile more suited to biodiesel conversion.…”
Section: Flotationmentioning
confidence: 99%
“…An increase in effectiveness was also demonstrated in the use of microbubbles for separation of substances by flotation (Coward et al, 2015, Hanotu et al, 2012. Microbubbles, by their strong clinging to contaminants like oil or grease, make possible efficient and environmentally friendly removal of fats in product cleaning.…”
Section: Applications and Importance Of Microbubblesmentioning
confidence: 99%
“…Microbubbles were also demonstrated by Xi (2012), to be efficient for disinfection by removal of pathogens. Coward et al, (2015) demonstrated efficient flotation harvesting of algae grown in bioreactors for producing biofuels.…”
Section: Applications and Importance Of Microbubblesmentioning
confidence: 99%
“…The higher the probability, the higher the efficiency of the flotation. A higher number of smaller bubbles can increase the surface area per volume so that the efficiency can be improved (Coward et al, 2015). A microbubble is defined as bubble that has diameter between 50200 µm .…”
Section: Introductionmentioning
confidence: 99%